Inmigración femenina, empleo y familia en una parroquia de la ciudad de México : Santa Catarina, 1775-1790 - Pescador, Juan Javier (El Colegio de México A.C., 1990)
The purpose of this article is to identify and evaluate the impacts of growing female in-migration to Mexico City at the close of the eighteenth century, analyzing for the case of the parish of Santa Catarina the proportion of men/women in the certificates of baptisms and burials -using as a basis the parish records taken house to house between 1779 and 1788-, discussing the impact that such an imbalance had on the formation of families, and concluding with astatement of some aspects of the Bourdon policy on urbanization and employment that had a direct bearing upon the configuration of said structure of sexual and family life.